2014
DOI: 10.1177/0218492314546028
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery antibiotic prophylaxis and calculated empiric antibiotic therapy

Abstract: This survey shows that existing national guidelines and recommendations concerning perioperative antibiotic prophylaxis and calculated empiric antibiotic therapy are well applied in almost all German heart centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…No specific risk factor was identified for Acinetobacter species-related early BSI in our patients, and Acinetobacter species-related BSI did not lead to a worse outcome. Efforts to reduce the incidence of Acinetobacter species-related BSI are identical to those widely accepted practical bundles, such as full barrier precautions for central catheters and avoiding unnecessary central venous catheters [6,16]. Nevertheless, efforts to prevent and adequately treat Enterobacteriaceaerelated BSI after cardiovascular operations should be emphasized and might require adjustments.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…No specific risk factor was identified for Acinetobacter species-related early BSI in our patients, and Acinetobacter species-related BSI did not lead to a worse outcome. Efforts to reduce the incidence of Acinetobacter species-related BSI are identical to those widely accepted practical bundles, such as full barrier precautions for central catheters and avoiding unnecessary central venous catheters [6,16]. Nevertheless, efforts to prevent and adequately treat Enterobacteriaceaerelated BSI after cardiovascular operations should be emphasized and might require adjustments.…”
Section: Commentmentioning
confidence: 99%
“…An associated operative mortality rate of up to 40% has also been reported when a bloodstream infection (BSI) develops in patients undergoing cardiovascular operations [3]. Many risk factors for postoperative infection after cardiovascular surgery using CPB have been identified, such as older age, diabetes mellitus, obesity, emergency operation, multiple blood transfusions, postoperative low cardiac output, and use of mechanical circulatory supporting devices [4,6]. Besides, use of CPB itself could be a theoretical risk factor for infection after a cardiovascular operation as a result of the increased blood transfusion and immunomodulatory effect of CPB.…”
mentioning
confidence: 99%
“…Interestingly, we know from experience that some patients develop fever and hemodynamic instability after cardiac surgery without definitive etiological evidence. Previous studies have shown that systemic inflammatory response syndrome and postoperative fever are complications that develop after cardiac surgery (3,4). We speculate that fever of unknown origin (FUO) and hemodynamic instability are related to systemic inflammatory response syndrome or sepsis.…”
Section: Introductionmentioning
confidence: 80%
“…However, they may not be. The use of CPB or extracorporeal life support (ECLS) to support a patient during an intraoperative thoracic surgery is common, and cardiopulmonary bypass (CPB) is one of the risk factors for infection in patients undergoing cardiac surgery ( 5 ). On the one hand, it is reported that most of the early bloodstream infections of patients undergoing CPB are caused by gram-negative bacteria, which are commonly present in the intestinal flora ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of postoperative infection in cardiac surgery patients may be complicated due to the difficulty in distinguishing the symptoms of infection from a systemic inflammatory response caused by extensive tissue damage or the use of cardiopulmonary bypass during surgery [ 10 ]. The clinical symptoms of SSI in cardiac surgery patients vary depending on the type of infection.…”
Section: Clinical Symptoms Of Ssismentioning
confidence: 99%